Developing EPQ models for non-instantaneous deteriorating items - Naser Ghasemi (Journal of Industrial Engineering International, 2015)
In this paper, the classical economic production quantity (EPQ) model is developed for non-instantaneous deteriorating items by considering a relationship between the holding cost and the ordering cycle length. Two models are developed. First, the proposed model is considered when backorders are not permitted and this condition is waived for the second case. The cost functions associated with these models are proved to be convex and an algorithm is designed to find the optimum solutions of the proposed model. Results show that the relationship between holding cost and ordering cycle length has a significant impact on the optimal lot size and total cost in the EPQ model. Numerical examples are presented to demonstrate the utility of the models.
Keywords: 650; Inventory; EPQ; Non-instantaneous deterioration; Holding cost